A new algorithm for kinematic program control of optical parts by grinding - Khang, Nguyen Van; Hung, Nguyen Trong (Vietnam Journal of Mechanics, 2010)
Based on the definition of the local coating coefficient, the average local coating coefficient and the speed coefficient in grinding of optical parts, and on theory of multibody kinematics, an algorithm for kinematic program control during the grinding process of optical parts has been developed at Hanoi University of Technology. Using this algorithm, the results of the improvement in the precision of processed surfaces of optical parts by grinding under kinematic program control have been obtained and will be presented in the present paper